Do different headache types present with varying MRI findings? (Annals of Medical Research, 2021)
Aim: Studies evaluating the magnetic resonance imaging findings in headache cases mostly focus on migraine and tension headache. In the current study, we aimed to evaluate the possible differences in the magnetic resonance imaging reports between the common headache types presenting with normal neurological findings. Materials and Methods: The magnetic resonance imaging findings of 170 patients aged between 18-45 years that presented with the complaints of headache were retrospectively evaluated. The patients with headaches were divided into the following groups: migraine, tension headache, medication overuse headache, and other headaches (cluster headache, hemicrania continua, paroxysmal hemicrania, trigeminal neuralgia), each consisting of 30 cases. Also, a control group was formed with 50 patients without a headache. The extracerebral, major and minor intracranial abnormalities were noted for all groups. The χ2 test was used to compare the data between the groups.Results: When the patients with headaches were evaluated, clinically silent brain infarct was detected as a major intracranial abnormality only in one patient with trigeminal neuralgia. The incidence of minor abnormalities was higher in the headache groups compared to the controls (p0.05). Conclusion: There was no significant difference between the headache types and the MRI findings. Increased white matter hyperintensity was present in patients with headaches, and especially those with migraine compared to the controls. Keywords: Primary headache; migraine; tension headache; medication overuse.